LEADERS’ SUPPLICATION BEHAVIOUR AND EMPLOYEES’ WORK-RELATED ATTITUDES IN MEDIA ESTABLISHMENTS IN RIVERS STATE - B. M. Nwibere (Journals Park Publishing, 2022)
This study, with practical implications, explored the relationship between leaders' supplication behavior and employees’ work-related attitudes in media establishments in Rivers State, Nigeria. A total of one hundred and fifty (150) employees were randomly sampled from fifteen (15) purposively drawn media establishments in Rivers State, Nigeria, encompassing newsprint, radio houses, and television houses. Adopting a cross-sectional survey approach, the study utilised the Kendall Correlation Statistical Technique for data analysis. With direct application, the findings revealed a significant and linear relationship between leaders’ supplication and employees’ work-related attitudes. Specifically, the results of data analysis revealed a positive and significant relationship between leaders’ supplication and employees' job satisfaction, commitment and involvement. Based on the findings above, the study concludes that leaders' supplication behaviour is crucial in shaping employees' work attitudes. Specifically, the study concludes that leaders' supplication behaviour significantly predicts employees’ job satisfaction, commitment and involvement in media establishments in Rivers State. This highlights the importance of leaders' supplication behaviour in shaping the work attitude of employees in media establishments. This implies that employees tend to be more motivated, committed and engaged when their leaders demonstrate supplication behaviour towards them. The theoretical and managerial implications of these findings were also discussed.
Keywords: Employees Commitment, Employee Involvement, Job Satisfaction, Leaders’ Supplication, Media Establishments, Rivers State.